Frequently Asked Questions about the Africanized Honey Bee in Florida - Michael K. O’Malley; James D. Ellis; Anita S. Neal (EDIS)
The African honey bee, Apis mellifera scutellata, was introduced into South America from the central and southern part of Africa in 1957. Since its introduction into South America, the African bee has migrated into the southwestern United States and Florida. Apis mellifera scutellata is the African bee subspecies referred to in this revised 3-page fact sheet, which answers commonly asked questions about these bees and their behavior. Written by M. K. O’Malley, J. D. Ellis, and A. S. Neal, and published by the UF Department of Entomology and Nematology, November 2014.